A Formaldehyde-free P-N Synergistic Flame Retardant Containing Phosphonate and Ammonium Phosphate for Cotton Fabrics. Issue 16 (28th November 2022) - Ding, Dan; Liu, Yunlan; Lu, Yanfeng; Chen, Yu; Liao, Ying; Zhang, Guangxian; Zhang, Fengxiu
ABSTRACT: A highly efficient and durable phosphorous–nitrogen (P-N) synergistic flame retardant containing ammonium phosphate active groups (AATMPEG) was synthesized and grafted onto cotton fabrics by P-O-C covalent bonding. In the synthesis process, the -P=O(OH)2 group on the flame retardant is esterified with ethylene glycol to reduce the influence of metal ions on the flame retardant of cotton fabric during washing. The limiting oxygen index (LOI) value of 25 wt% AATMPEG-treated cotton fabric reached 45.0% and remained at 33.0% after 50 laundering cycles (LCs). Scanning electron microscopy (SEM), energy dispersive X-ray spectrometer (EDS), and X-ray diffraction (XRD) results showed that the flame retardant successfully penetrated the fabric without affecting its surface morphology and crystal structure. Thermogravimetry (TG), cone calorimetry, and vertical flammability test results show that AATMPEG generates phosphoric acid or polyphosphoric acid during combustion, promoting the thermal degradation and dehydration of the cotton fabric. The AATMPEG does not use formaldehyde in the synthesis process, meeting environmental requirements.